Moral disengagement and self-reported harassment proclivity in men: the mediating effects of moral judgment and emotions. Issue 2 (4th May 2018) - Page, Thomas E.; Pina, Afroditi
ABSTRACT: Three online studies investigated the association between moral disengagement and men's self-reported harassment proclivity. Participants (total N  = 336) were required to read a vignette depicting either quid pro quo harassment (studies 1 and 2) or hostile work environment harassment (study 3). A salience manipulation was used in each study to explore the causal directionality of this association. The mediating effects of moral judgment, negative affect (guilt and shame) and positive affect (happiness) about the harassment were also assessed as participants were asked to imagine themselves as the harassment perpetrator. Across the three studies, it was shown that moral disengagement had an indirect effect in predicting men's proclivity to harass by lowering their moral judgment and negative affect about the harassment, conversely amplifying positive affect. Overall, the findings support social cognitive theory, indicating that moral disengagement may enable people to self-regulate their own behavioural inclinations to harass.